(untitled) (Bangladesh Journal of Neuroscience, 2018)
Background: Stroke is the third most common cause of death in the developed world after cancer and ischaemic heart disease, and is the most common cause of severe physical disability. Although, there are many patients in Bangladesh suffering from these disorders, systematic research on them, especially serum biological markers of ischaemic stroke are yet to be evaluated. So the objectives of the present study are to see the serum d-dimer among acute ischaemic stroke patient. Methods: This is a hospital based cross sectional study conducted in neurology department of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. Total 162 cases of acute ischaemic stroke irrespective of their gender were included who were admitted in BSMMU during the period from October, 2012 to October, 2013. Blood sample was taken for d-dimer measurement from each patient and d-dimer was estimated in department of haematology, BSMMU. Results: Among 162 patients with acute ischaemic stroke, it showed that d-dimer level mean was 1.0862 mg/L ± SD 0.9844 with maximum 4.4 and minimum 0.01. D-dimer was highly raised (n=75, 46%; mean 1.6519 ± SD 1.1396; min 0.11 and max 4.4) in early days of 1st week with a descending manner and almost reached normal level (n=87, 54%; mean 0.5986 ± SD 0.4210; min 0.01 and max 2.25) in later half of 2nd week. Conclusion: The study showed that raised d-dimer (DD) was significantly associated total anterior circulation infarction (TACI) & partial anterior circulation infarction PACI and raised DD was significant differentiating point TACI or PACI from lacunar infarction (LACI) & posterior circulation infarction (POCI) and raised D-Dimer might not differentiate between TACI & PACI. Bangladesh Journal of Neuroscience 2018; Vol. 34 (1): 25-31